"Clickable" bacterial poly(γ-glutamic acid). Issue 35 (30th July 2020) - Cedrati, Valeria; Pacini, Aurora; Nitti, Andrea; Martínez de Ilarduya, Antxon; Muñoz-Guerra, Sebastián; Sanyal, Amitav; Pasini, Dario
Abstract : The controlled functionalization of bacterial γ-PGA is realized through sonication, solubilization using quaternary ammonium salts and click chemistry. Abstract : Poly(γ-glutamic acid) (γ-PGA) is one of the few bacterial polymers in nature; as such, it possesses the added value of a "green birth" (fermentation) and "green death" (biodegradability), which is ideal for sustainable macromolecular platforms. Efficient functionalization strategies are required in order to transform the native bacterial biopolymer into a material with tailored properties for bulk scale or biomedical applications. We report on a novel approach to the facile functionalization of bacterial γ-PGA, realized with several levels of control: (a) the modulation of the molecular weight through sonication, and the solubilization in organic solvents through counterion exchange with suitable quaternary ammonium salts, (b) the introduction of reactive functionalities through reactions in homogeneous conditions in organic solvents, to afford homo- or copolymers; (c) a second tier functionalization using copper(i )-catalyzed alkyne–azide cycloaddition (CuAAC) click chemistry.